The role of metabolic reprogramming in immune escape of triple-negative breast cancer - Bao, Ruochen; Qu, Hongtao; Li, Baifeng; Cheng, Kai; Miao, Yandong; Wang, Jiangtao (Frontiers in Immunology, 2024)
Triple-negative breast cancer (TNBC) has become a thorny problem in the treatment of breast cancer because of its high invasiveness, metastasis and recurrence. Although immunotherapy has made important progress in TNBC, immune escape caused by many factors, especially metabolic reprogramming, is still the bottleneck of TNBC immunotherapy. Regrettably, the mechanisms responsible for immune escape remain poorly understood. Exploring the mechanism of TNBC immune escape at the metabolic level provides a target and direction for follow-up targeting or immunotherapy. In this review, we focus on the mechanism that TNBC affects immune cells and interstitial cells through hypoxia, glucose metabolism, lipid metabolism and amino acid metabolism, and changes tumor metabolism and tumor microenvironment. This will help to find new targets and strategies for TNBC immunotherapy.